A tolbutamide–metformin salt based on antidiabetic drug combinations: synthesis, crystal structure analysis and pharmaceutical properties. Issue 9 (14th August 2019) - Jia, Lina; Wu, Songgu; Gong, Junbo
Abstract : A drug–drug anhydrous salt containing tolbutamide and metformin was created based on drug combinations for type 2 diabetes. Pharmaceutical property alterations were associated with the crystal packing features and potential hydrogen‐bonding sites through observed changes in the crystal structures. Abstract : A drug–drug anhydrous pharmaceutical salt containing tolbutamide {systematic name: 3‐butyl‐1‐[(4‐methylbenzene)sulfonyl]urea, TOL, C12 H18 N2 O3 S} and metformin (systematic name: 1‐carbamimidamido‐ N, N ‐dimethylmethanimidamide, MET, C4 H11 N5 ) was created based on antidiabetic drug combinations to overcome the poor pharmaceutical properties of the parent drugs. Proton transfer and the proportion of the two components were confirmed by 1 H NMR spectroscopy and single‐crystal X‐ray diffraction analysis. Comprehensive characterization of the new pharmaceutical salt crystal, 2‐[(dimethylamino)(iminiumyl)methyl]guanidine (butylcarbamoyl)[(4‐methylbenzene)sulfonyl]azanide, C4 H12 N5 + ·C12 H17 N2 O3 S −, was performed and showed enhancement of the pharmaceutical properties, such as lower hygroscopicity and greater accelerated stability than the parent drug MET, and higher solubility and dissolution rate than TOL. The property alterations were correlated with the crystal packing features and potential hydrogen‐bonding sites through observed changes in the crystal structures.